OVERVIEW OF RANDOMIZED CONTROLLED TRIALS - RAJAGOPALAN, RATHAI; M.DEODURG, PRIYADARSHINI; SRIKANTH (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Randomized controlled trials are considered to be the gold standard in clinical studies to establish level of evidence in medical research. But, they are not easy to conduct and various other aspects have to be looked into. Randomization offers each enrolled subject equal chance of being allocated to the intervention and the control groups. Randomized control trial (RCT) is most powerful tool in clinical research. In this, subjects Â are assigned to different groups of interventions by chance for comparison. RCT is only study design which can help us evaluate a new treatment. Â By assigning participants to different intervention groups by chance, comparison between the interventions groups is made. Purpose of randomization is to make the treatment groups comparable, eliminates the source of and it ensures that the difference in groups is only due to trial treatments. In this article, we review randomized control trial with special emphasis on various types of randomized controlled trials, their characteristics, the process of randomization, and advantages and drawbacks of randomized controlled trials. Key words:Randmized controlled trials, study design, randomization, clinical research